North Korea’s ICBMs: What Now? - Nah, Liang Tuang (2017)
North Korea’s Intercontinental Ballistic Missiles (ICBMs) hardly change the overall USDPRK strategic calculus. The only practical policy course is to implement isolative strategies that limit the threat from Pyongyang.